Skin disease detection and classification using deep learning - Shuvon, Mehedi Hasan; Sadia, Rowshanara; Shormi, Shanjida Habib; Arafin, Umma Tania; Chowdhury, Md. Rawha Mikdad (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.